Sustainability reporting software in the scope of csrd - developing a prototype for social issues - Linyan, Li (2023)
This thesis explores the development of sustainability reporting software, with a focus on the Corporate Sustainability Reporting Directive (CSRD). As a group part, it comprehensively evaluates existing software solutions, examining their key features and assessing their alignment with CSRD standards. Incorporating expert interviews and competitor analysis, the study uncovers existing gaps and potential future advancements in the field. As an individual part, the research integrates the development of software prototypes. It also discusses challenges and opportunities in sustainability software, providing valuable insights and recommendations for future research and development.